The Use of EACA in Preventing or Reducing Hemorrhages in the Hemophiliac - Reid, W. O; Hodge, Shirley Mae; Cerutti, E. R (Thrombosis and Haemostasis, 1967)
Thirty one hemophiliacs of all grades of severity have been evaluated clinically and with laboratory tests to ascertain the preventive and therapeutic effectiveness of EACA, a plasminogen activator inhibitor, in reducing or eliminating hemorrhage. In an earlier study with one group of 14 patients, having a total of 40 dental extractions, no transfusions were needed after the surgical procedure as long as EACA treatment was continued through the healing period.In the present study, 17 severe (Grade III and IV) hemophilia A patients were placed on long term EACA dosage to observe possible hemorrhage preventive effects. The duration of treatment varied from 2-16 months. Improvement of all clinical criteria as defined in the text was statistically significant in both Grade III and IV hemophiliacs. The PTT, Hicks Pitney test and prothrombin consumption tests all showed statistically significant changes towards normal in the Grade IV hemophiliacs and the Hicks Pitney was significantly improved in the Grade III hemophiliacs. All three tests are sensitive to deficiencies of thromboplastin whether due to a failure of thromboplastin generation or an excess of an antithromboplastin or both. The data suggest that EACA can significantly reduce the incidence and severity of hemorrhage in the hemophiliac, if it is given in adequate continued dosage, thereby decreasing the morbidity associated with the disease.